Trends in the Use of Digital Stethoscopes in Healthcare: A Bibliometric Analysis - Mustopa, Acep Hidayatul; Saryono, Saryono; Setiawan, Henri; Masruah, Iim Imas (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study aims to review the scientific literature that has been conducted and published regarding the development of one of the medical devices, namely digital stethoscopes and look for novelty as a basis for conducting research. Methods: This research is a descriptive analysis with a bibliometric analysis approach. Searches for published articles were conducted in August 2023 on the Scopus and Pubmed databases through the Publish or Perish application from 2000-2023. Results: Of all the literature and publications that have been analyzed and mapped using VosViewer, the majority of studies found focus on discussing the use of digital stethoscopes in listening to and interpreting heart sounds compared to interpreting lung sounds. Conclusion: Based on the articles collected and processed in VosViewer, the results of this study, which can be used as a reference or basis for researchers, are about digital stethoscope innovations that focus on recording and interpreting lung sounds.